Pregnancy Related Acute Kidney Injury at a Tertiary Care Center in Nepal - Paudyal, P; Pradhan, N; Bista, KDB; Rawal, S (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This was performed to study the characteristics of Pregnancy Related Acute Kidney Injury (PRAKI), its management and outcome in patients at a tertiary level referral centre. Methods: A hospital based prospective observational study was conducted in Tribhuvan University Teaching Hospital (TUTH) over a period of 18 months. All patients diagnosed with PRAKI were included in the study. Patient profiles in terms of age, parity, gestational age were studied along with time of occurrence of PRAKI, preceding event, etiology, management and maternal outcome. Descriptive and univariate analyses were conducted and qualitative variables were expressed as percentages while quantitative variables as means. Results: There were fifteen cases of PRAKI during the study period with incidence of 2.1 per 1000 deliveries. The average age was 25.23± 3.8 years and 9(60%) were primipara. Fourteen (93.3%) developed PRAKI in the postpartum period with 10(66.6%) cases following Lower Segment Caesarian Section (LSCS). The commonest etiology of PRAKI was severe preeclampsia/ Hemolysis, Elevated Liver enzymes, Low Platelet (HELLP) syndrome and pregnancy hemorrhages each consisting 4(26.6%) cases. The stage of Acute Kidney Injury (AKI) according to RIFLE (Risk, Injury, Failure, Loss, ESRD-End Stage Renal Disease) criteria was as follows: risk in 1(6.6%), injury in 3(20%) and failure in 11(73.3%) cases. Hemodialysis was necessary in 12(80%) cases while 3 cases (20%) improved with medical management only. The average duration of hospital stay was 25.2±14.7 days and 7(46.6%) needed ICU admission. Twelve (80%) cases recovered completely while two patients were dialysis dependent at the time of evaluation. There was one death. Conclusions: PRAKI occurred mainly in the postpartum period with severe preeclampsia/HELLP syndrome and hemorrhages as the most common causes. It is associated with high maternal morbidity, prolonged hospital stay and even mortality. Multidisciplinary team management is essential.